GR_GERICHTE ZR2 2024 54 vom 13. März 2025 , Arbeitslosenversicherung - GR Gerichte (2025)
Einsichtnahme in den Geschäftsbericht nach Art. 958e Abs. 2 OR | OR 927-964L Handelsregister/Geschäftsfirmen/kaufmännische Buchführung